EFEKTIFITAS EKSTRAK ETANOL KULIT NANAS (Ananas Comosus L. Merr) terhadap Trichophyton mentaghrophytes - Siti Juariah; Mega Pratiwi Irawan; Yuliana Yuliana (LPPM Universitas Abdurrab, 2018)
Ringworm of the skin caused by a Trichophyton mentaghrophytes, Drugs that are commonly used are synthetic drugs, synthetic drugs can have a negative impact. By because it, research on natural antifungal substances continue to do that with the use of pineapple skin.A pineapple skin waste processed pineapple industry, namely the remainder of the meat and fruit contains secondary metabolites are flavonoids, phenolics, saponins, triterpenoids, steroids and alkaloids. The purpose of this study to determine the content of secondary metabolites contained in the pineapple skin and for the inhibition of Trichophyton mentaghrophytes using experimental laboratoryin vitro. Pineapple bark extract prepared in various concentrations of 10%, 15%, 20% and 25%, then test the inhibition ofTrichophyton mentaghrophytesand incubated temperature 25o C for 5day. Based on the results obtained percentage pineapple skin extractfungal inhibition test Trichophyton mentaghrophytesthe concentration 10%, 15%, 20% and 25%, respectively, are22%, 37%, 46% and 56% compared to the positive control.Based on this research, pineapple bark extract containing flavonoids, phenolics, saponins, triterpenoids, steroids and alkaloids. The results of this study can be concluded that the extract of pineapple skin Trichophyton mentaghrophyteswhich is characterized by the formation of inhibit zone.